Analysis Of The Effect Of Mass Variation On The Coefficient Of Friction On Wood - Munthe, Clara Dwipuan; Syifa, Aliyya Layyinatu; Setiaji, Bayu (Pascal: Journal of Physics and Science Learning, 2024)
The purpose of this study is to determine the coefficients of kinetic and static friction in order to identify areas where we can reduce unwanted friction, thereby enhancing the performance and efficiency of various devices or machines we use daily. This research employs a quantitative approach with an experimental design or practical activities conducted in a laboratory or controlled environment, where specific variables can be accurately measured. The collected data will be analyzed in numerical or statistical form. The values indicate that the kinetic friction coefficient between wood and wood is the smallest, at 0.14. The kinetic friction coefficient between metal and wood ranges from 0.28 to 0.30. This means that the kinetic friction force acting on a wooden block on a wooden surface is the smallest compared to other materials. The static friction coefficient between wood and wood is the highest, at 0.40. The static friction coefficient between metal and wood ranges from 0.23 to 0.32. This indicates that the static friction force required to initiate the movement of a metal object on a wooden surface varies depending on the mass of the metal.